Envisaging change in maize farming: the push and pull factors - Whitfield, Stephen; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Participatory and deliberative approaches were used in order to draw out and evaluate pathways of adaptation in maize farming in the Kenyan districts of Makueni (in Central Province) and Nandi/Nyando (in Western Province), whilst allowing participants to reflect on and share their own perceptions, experiences, and expectations of future change.